A study on the local corrosion behavior and mechanism of electroless Ni–P coatings under flow by using a wire beam electrode. Issue 59 (23rd October 2019) - Tang, Yi-Rong; Wang, Qin-Ying; Pei, Rui; Xi, Yu-Chen; Dong, Li-Jin; Bai, Shu-Lin; Wan, Shanhong
Abstract : The local corrosion behavior and mechanism of Ni–P coatings in an NaCl solution with different flow speeds were investigated through a wire beam electrode with morphological, elemental and electrochemical analyses as well as numerical simulations. Abstract : The local corrosion behavior and mechanism of Ni–P coatings in a 3.5 wt% sodium chloride solution with different flow speeds (0 m s −1, 0.5 m s −1, 1 m s −1 ) were investigated through a wire beam electrode (WBE) with morphological, elemental and electrochemical analyses as well as numerical simulations. It was found that the microstructure of the Ni–P coating was in the shape of broccoli and possessed satisfactory compactness and uniformity. The numerical simulations showed that the speed increased and the static pressure decreased at the local area. Combined with WBE, it was found that the average corrosion potential decreased at that area. The results indicated that the corrosion tendency and corrosion rate of the Ni–P coating were larger at higher speeds, and the corrosion resistance could be improved by the electroless Ni–P coating. WBE was helpful in revealing the local electrochemical information of the Ni–P coating.